Ritual kematian dan duka selama pandemi COVID-19: Respons keluarga Bali - I Wayan Suyadnya; Luh Ayu Tirtayani; Arief Setiawan; Alies Poetri Lintangsari (Institut Seni Indonesia Denpasar, 2022)
The unprecedented COVID-19 pandemic leaves great number of human deaths since its first emergence. The Balinese that praise death through rituals should make some adjustment as there are some religious and traditional activities restriction to mitigate the COVID-19 pandemic. Studies on human rituals have indicated lifelong changes, including in funeral rituals. This research addresses the meaning and adjustment of the death rituals employing various sources and perspectives. Benefiting the investigative study, this research explores the impacts of the COVID 19 pandemic to the adaptation of death rituals practices by the Balinese. The research was conducted in Tabanan in the period from May-September 2021. The qualitative research design with focus on observation, in-depth interviews, and visual documentation of family members who lost other family members due to COVID-19 was employed. Data analysis was performed through inductive thematic analysis for data interpretation. Research results indicated that the experience of the sudden loss of family members due to COVID-19 is worsened because of the absence of the proper funeral rituals. The absence of rituals eliminates the social connections and social functions as it serves function as the social-cultural support to accept death. Additionally, it also diminish the grieving period as well as reducing the role of the traditional social institutions (desa adat) as the social-cultural supporter. This paper offers the deeper elaboration on how the Pandemic Covid-19 has affected the Balinese in overcoming death both socially and culturally.